Managerial Economic Strategies In Improving Micro Business - Ulul Azmi; Sri Murtiana; Guntur Eko Saputro (CV. AFDIFAL MAJU BERKAH, 2024)
Greenhouse Gas (GHG) emissions are gases released into the atmosphere from various human activities on earth which cause a greenhouse effect in the atmosphere. These greenhouse gases are carbon dioxide (CO2), sulfur dioxide (SO2), nitrogen monoxide (NO), nitrogen dioxide (NO2), methane gas (CH4), and chlorofluorocarbons (CFC). Carbon gas as the main pollutant is produced from burning oil, coal and other organic fuels. To reduce this negative impact, each country then ratified the Paris Agreement and committed to keeping the temperature increase to less than 2 degrees Celsius. In this regard, each country targets reducing GHG emissions, especially carbon, within a certain period of time. The Indonesian government has set a target to reduce carbon emissions from all sectors by 2030 by 29 percent with its own efforts or up to 41 percent with funding assistance from abroad. In the 41% reduction target, the government hopes to collaborate with developed countries that have high levels of carbon emissions, through a